Las guerras civiles: consideraciones teóricas desde las Ciencias Sociales - Eduardo González Calleja (Amnis)
Since the Cold War, social scientists started the systematic study of the phenomenon of civil war, but for nearly half a century his analysis was subsumed and partly hidden by the logic of bloc politics. The end of the bipolar system unmasked some revolutionary wars of national liberation that were, simply, civil wars. That’s when systematic analysis of internal armed conflicts began. This paper analyzes the problems of defining such conflicts; their classification in “classical” conventional wars and “new” low intensity wars; hypotheses about their origin, duration and recurrence; violent dynamics that generate, and possible avenues of resolution through intervention, negotiation or peacemaking. We conclude that the systematic study of civil wars are taking their first steps, and that this phenomenon must be analyzed as a high cost strategy aimed at the conquest of power, revolution, counterrevolution, or the elimination of the adversary. While their origins, development and objectives are political problems, we must not forget other manifestations, such as the confrontation of war strategies, legal and strategic implications and the aftermath of these internal conflicts in the international scene.